Fatores críticos de sucesso em gestão de projetos cloud computing e a relação com o sucesso de projetos: proposição de um modelo teórico empírico - Correia, Silvia Regina Veronese (2024)
The traditional local model for managing Information Technology (IT) applications and infrastructure has proven to be inefficient, characterized by the utilization of expensive technology equipment with inadequate capacity to meet organizational demands. In response, companies are increasingly shifting towards cloud computing. Cloud Computing necessitates a well-defined environment, a value-driven strategy, and coordinated execution by both IT and business entities to attain return on investment. This entails reevaluating project management methodologies within this new model. Despite an extensive literature on critical success factors (CSFs) in IT projects, limited attention has been devoted to the cloud context and its influence on project success. Consequently, this thesis aims to address the following research question: How is the relationship between critical success factors in cloud computing project management and the success of these projects established? The thesis comprises multiple studies. Initially, an integrative literature review was conducted to facilitate a comparative analysis of CSFs in IT project management, cloud adoption project management, and cloud projects, thereby identifying the primary CSFs in cloud computing project management. For the second study, which aimed to identify the CSFs in cloud computing project management and their relationships with project success, the methodology employed was a survey research, incorporating principal component analysis, structural equation modeling, and artificial neural networks. The research involved professionals engaged in cloud computing projects, with the objective of elucidating the relationships between critical variables and project success, as well as highlighting the success rates of cloud projects. The principal theoretical contribution of the thesis lies in enriching existing literature encompassing critical success factors, cloud computing, and project success, alongside the development of a theoretical model delineating the critical success factors and their significance in cloud project success. In terms of practical contribution, this study has yielded a software-based technical product offering guidance to project managers on the essential factors conducive to the success of such projects, in addition to generating a technological article elucidating the success of cloud projects.